Efektivitas Pijat Endorphin Dan Countour Presure Terhadap Nyeri Persalinan Di Klinik Annisa - Yuni, Junia Setiyowati; Septa Rini, Ageng; jayatmi, Irma (Universitas Muhammadiyah Klaten, 2025)
Introduction: Labor pain is a physiological process, which occurs due to contractions due to internal hormonal processes childbirth such as increased oxytocin levels, increased prostaglandin levels and decreased progesterone levels. Efforts that can be applied to reduce labor pain in the first stage are non-pharmacological methods, one of which is endorphin massage and counter pressure. Objective: To determine the effectiveness of endorphin massage and counter pressure on the intensity of labor pain in the active phase of the first stage. Method: Using a before and after quasi-experimental design with 30 respondents divided randomly into two groups, namely group A received endorphin massage therapy, group B received countour pressure massage therapy. Results: Between the two groups, the normality value tested with the Shapiro Wilk showed a p- value>0.05 and the parametric statistical test paired T Test showed a p-value <0.05. Conclusion: giving endorphin massage and countour pressure has been proven to be able to reduce the intensity of labor pain during the first active phase. Keywords: Endorphin, Countour Pressure, Labor Pain